Methyl xanthine as a potential alternative to gibberellic acid in enhancing fruit set and quality in clementine citrus trees in spain - Quinones, Ana; Martínez-Alcántara, Belén; San-Francisco, Sara; García-Mina, José M.; Legaz, Francisco (Cambridge University Press, 2020)
Citrus clementine cv. ‘Nules’ is a seedless mandarin with excellent quality for consumption as fresh fruit; however, its poor fruit set leads to an excess of small-sized fruits. Currently, the only available practice to increase fruit set is the use of the growth regulator gibberellic acid (GA3) as a foliar spray. A trial was conducted to compare an environmentally friendly new bioregulator (MX), containing methyl-xanthine, to GA3 in terms of increasing fruit set and yield of clementine cv. Nules mandarin trees. Fruit yield was significantly increased in treated trees from 17.4 to 25.7% for GA3 and MX treatments, respectively, compared to untreated control trees, without any significant differences between the growth regulators. At the tested doses, MX performed similarly to GA3 in terms of fruit quality and nutrient content, while colour index was not affected significantly by this new bioregulator. A single foliar application of MX was enough to increase fruit set. Spray application ofMX on clementine mandarins at the end of the flowering period, when all petals have fallen showed a similar response to GA3 treatments